Hypercalcemia in malignant disease – pathophysiology, diagnosis and treatment - Wawrocka-Pawlak, Marlena; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2003)
Hypercalcemia is one of the most common life-threatening metabolic complications in patients with cancer. It occurs in approximately 10 to 20 percent of patients with malignant disease. Hypercalcemia is most commonly seen in association with multiple myeloma, squamous carcinoma of the bronchus, and breast cancer. Parathyroid hormone-related protein (PTH-RP) is a potent mediator of hypercalcemia. Small amounts of PTH-RP produced by normal tissues act locally as cytokines. When produced in large amounts by cancers, PTH-RP circulates in blood in sufficiently large amounts to act as classic hormones. A number of other soluble factors have been isolated that are potent inducers of bone resorption and hypercalcemia in particular cancers. Transforming growth factors (TGFs) are released in an autocrine manner by many cancer cells and regulate bone resorption and formation of normal bone. Active metabolites of vitamin D may be involved in the development of hypercalcemia in patients with lymphoma and myeloma. Prostaglandins may have an important role in cancer-related osteolysis. Interleukin-6 acts as an autocrine growth factor in myeloma, and may be associated with hypercalcemia in kidney cancer. Experimental and clinical data suggest that a receptor activator of NF-kappaB ligand (RANKL) may be an important factor mediating the bone destruction and hypercalcemia in patients with myeloma. In patients with evolving hypercalcemia, fatigue, lethargy, constipation, nausea, and polyuria are the most common initial complaints. Volume expansion with normal saline is a useful first treatment of hypercalcemia. The use of furosemide should be restricted to balancing fluid intake and urinary output in patients who have been fully rehydrated. Bisphosphonates have become the most commonly used drugs in the treatment of hypercalcemia. Intravenous infusion of 4 mg of zoledronic acid is more effective than infusion of pamidronate.